Sistem Informasi Pelayanan Umum pada Desa Benteng Kota Berbasis Web dengan Metode RAD - Agus Dendi Rachmatsyah; Feri Prasetyo H; Fitriyanti (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2020)
Benteng Kota village office is a village located in Tempilang District, West Bangka Regency. At the Benteng Kota village office the processing of population public services is still done manually. Therefore this website is made to facilitate the administration in handling public population services. The method used by the authors in this study is the Rapid Application Development (RAD) method. This system uses the PHP programming language with MySQL database. In implementing this existing system, it must be uploaded on the webserver so that it can be accessed in cyberspace. Because the implementation of the system is only a trial, the authors use XAMPP for the webserver. The tools used are object oriented (UML) tools. Based on the above problems, one alternative to this problem is to create a computerized system that will certainly make it easier. With the application of the existing population general service information system, it can overcome the problems and improve the work process which is still slow so that it is now faster and the handling in verifying caused by the feasibility of the village apparatus is also better.